Focal invasiveness in complete histological analyses of a large acral lentiginous melanoma - Xavier-Júnior, José Cândido Caldeira (Diagn Pathol, 2015)
BACKGROUND: Acral lentiginous melanoma is a melanoma with poor prognosis which is frequently diagnosed at an advanced stage. Since the thickness of tumour is one of the main prognostic factors, this case can exemplify how important complete histological analyses looking for focal invasiveness can be. CASE REPORT: A 77 year-old woman with a black spot with slow progressive growth on the left plantar region. She sought medical attention due to the expansion onto the dorsal surface of toes. The lesion had irregular borders and had spread to half the plantar surface. Histopathology confirmed the clinical suspicion of acral lentiginous melanoma Clark level IV and 2.6 mm Breslow thickness. The surgical specimen was entirely processed for histological evaluation, requiring 53 slides. Tumor dermal invasion was detected in only three out of 53 glass slides as the invasiveness was not identified by clinical, dermatoscopy or macroscopy exams. CONCLUSION: Sectioning through the entire lesion is considered very important to determinate the appropriate stage of the disease and the correct treatment and patient follow-up. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1513617994148349.